2019
DOI: 10.1111/inr.12501
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ disaster preparedness and core competencies in Turkey: a descriptive correlational design

Abstract: Aim This descriptive correlational study aimed to identify nurses’ perceptions of their own disaster preparedness and core competencies. Background As disasters have increased in number and severity in recent years, it is crucial that nurses should be appropriately prepared. There is still limited research on this issue in Turkey. Introduction With changes in disaster policies in the last decade, the need to improve the disaster core competencies of nurses has also increased. Methods A sample of 406 nurses sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
49
2
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(67 citation statements)
references
References 26 publications
11
49
2
5
Order By: Relevance
“…In contrast, response competencies differed by participants' age, education level, rank and career length. These results correspond to the findings of a previous study that reported differences by nurses' age, career length, rank and disaster experience (Baker, Alamri, & Aboshaiqah, 2019;Taskiran & Baykal, 2019). For future studies, nursing position differences should be measured to identify whether the differences arise from roles and responsibilities in an emergency or from increased training opportunities.…”
Section: Discussionsupporting
confidence: 86%
“…In contrast, response competencies differed by participants' age, education level, rank and career length. These results correspond to the findings of a previous study that reported differences by nurses' age, career length, rank and disaster experience (Baker, Alamri, & Aboshaiqah, 2019;Taskiran & Baykal, 2019). For future studies, nursing position differences should be measured to identify whether the differences arise from roles and responsibilities in an emergency or from increased training opportunities.…”
Section: Discussionsupporting
confidence: 86%
“…In contrast to this result, from a three-state survey on disaster behavior health, findings demonstrated that there is a need for improved disaster behavioral health training and response plan [20]. From the perspective of professionals, technical skills scored highest, and critical thinking skills scored lowest from a survey regarding the perception of own disaster preparedness and core competencies [21]. Another study presented some issues related to the training development for NGO workers, especially in the Chinese community, and highlighted the alignment of training with the organization's vision and mission [22].…”
Section: Literature Reviewmentioning
confidence: 65%
“…Again, there were differences found in the responses in terms of the community and the number of family members. Parallel to the findings of this study, a study provided statistical differences in their research when the total and sub-scale scores were compared by age group, professional experience, working position, and prior disaster experiences [21].…”
Section: Discussionmentioning
confidence: 80%
“…This research design is used to ascertain the interplay between and among variables. In essence, it examines the patterns in data but does not in any way prove any causative effect (Omair, 2015;Taskiran & Baykal, 2019).…”
Section: Methodsmentioning
confidence: 99%